Redesigning Olefin Metathesis Catalysts for Chemical Biology - Blanco Barrios, Christian O' Bryan (Université d'Ottawa / University of Ottawa, 2025)
Olefin metathesis is arguably the most versatile method yet developed to forge carbon-carbon bonds in chemical biology. Its power rests on the formation of an alkene linker that is not only the smallest, simplest, most flexible such connecting group attainable, but one that is inert under physiological conditions. Additional advantages stem from the reduced toxicity of ruthenium, relative to other transition metals in routine use, of which copper is most notoriously problematic. All of these are key strengths over alternative bond-forming methods such as click chemistry and cross-coupling. Beyond merely conjugation, olefin metathesis is uniquely suited to the assembly of conformationally flexible macrocycles. The latter include macrolides now emerging as a major class of antiviral and oncology therapeutics, and as probes for understanding biological processes. Nevertheless, applications of metathesis in these demanding contexts are largely confined to proof-of-concept studies, owing to facile catalyst degradation. Many view the fundamental challenge as the abundance of functional groups present. This thesis work began with an alternative hypothesis: that water - the native solvent of chemical biology - is potentially the major contributor to catalyst decomposition. By identifying and addressing decomposition events via a mechanism-driven approach, this thesis establishes a robust foundation for understanding in aqueous metathesis, which is anticipated to open up new opportunities in chemical biology. Decomposition by trace water in organic solvents was examined first, to isolate the problem from the broader complexities presented by aqueous environments. Trace water was shown to significantly reduce metathesis productivity, even for benchmark substrates that deliver turnover numbers in the tens of thousands in anhydrous media. Evidence was presented for accelerated decomposition via β-H elimination and bimolecular coupling of the active species. Ligand design to block these pathways correlated with metathesis productivity, providing a foundation for rational design for enhanced performance in water. Coordination of water to the catalyst to form transient aqua species was posited, with hydrogen-bonding of the water ligand underlying both β-H elimination and bimolecular coupling. Subsequent studies focused on metathesis in bulk water, using the water-soluble catalyst that overwhelmingly dominates current use. In this catalyst, cationic ammonium groups are used to confer solubility in water. Posited as a key weakness is the charge buildup associated with the cationic ligand, in conjunction with the initial aquation step. Charge buildup drives formation of hydroxide species that participate aggressively in catalyst decomposition. Speciation studies revealed that the aqueous chemistry of the catalyst is governed by dynamic equilibria involving aqua, hydroxide, and chloride species, which are strongly influenced by pH and chloride concentration. Low chloride levels permit hydroxide formation: higher chloride concentrations suppress hydroxide species, but compromise catalyst solubility, owing in part to the common-ion effect. Building on these insights, a new family of water-soluble catalysts was developed. Anionic sulfonate groups were introduced to improve solubility, to inhibit hydroxide formation, and to limit the affinity of the ruthenium center for negatively-charged biological functionalities, including DNA. The sulfonate catalysts exhibited breakthrough productivity in metathesis of unprotected nucleoside and carbohydrate substrates in water. They also enabled, for the first time, on-DNA metathesis in bulk water, with minimal DNA degradation. These advances highlight the strengths of mechanistically-guided catalyst design - and, more specifically, the understanding of catalyst decomposition - in addressing challenges that have limited opportunities to date. Olefin metathesis is now poised to open new areas of chemical space. A specific consideration in this thesis are opportunities for drug discovery via DNA-encoded libraries and oligonucleotide-based therapeutics. More broadly, however, transformative advances can be anticipated at the frontiers of biology and medicine.
Keywords: Olefin Metathesis; Aqueous Chemistry; Chemical Biology; Ruthenium; Mechanistic Studies; Catalyst Redesign; Oligonucleotide modification